MONITORING APPLICATION SYSTEM DEVELOPMENT AND EVALUATION OF “PUPR” DEPARTMENT OF GENDER LEADING ACTIVITIES IMPLEMENTATION - Ramacos Fardela; Arif Rizki Marsa; Lilik Suhery; MS Firman Maulana (J-ICON : Jurnal Komputer dan Informatika, 2023)
Monitoring and evaluation are the jobs that are often done by the Payakumbuh Public Works Department to maximize work in the field. The Payakumbuh Public Works and Public Housing (PUPR) Office itself is experiencing difficulties in monitoring and evaluating work in the field that is currently underway and the activities carried out have been realized. So far, office work has been monitored manually one by one because the Payakumbuh (PUPR) does not have an information system that can monitor and evaluate all work simultaneously and provide an overall target picture yet. In activities, especially work at the Payakumbuh PUPR Service, it applies the application of gender mainstreaming ("PUG"). The Ministry of Public Works of the Republic of Indonesia as the target for PUG implementation is the integration of a gender perspective into the internal culture of the Ministry of Public Works (at the central and regional levels) to produce an institutional culture that is sensitive to gender issues. To monitor this, applications are developed using the Agile Development software system development methodology. Researchers designed this website application to overcome this problem. The system was built using the PHP programming language with the Laravel Framework. The results showed that the application of reports on the implementation of gender mainstreaming activities with the Laravel Framework helped website developer performance to be more effective and efficient than using the static PHP programming language. The Laravel framework supports is object oriented and supports all databases. The Uniform Resource Locators (URL) structure used in Laravel is much more flexible and much easier to change in routing.